Organizational leadership and justice's impact on organizational commitment - Ferdinandus Sampe; Rian Ardianto; Warkianto Widjaja (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the influence of leadership and organizational justice on organizational commitment. This research was conducted at a manufacturing company located in Bandung, West Java. The study used 85 respondents who were employees of a manufacturing company in Bandung. In this study the sampling technique used non-probability sampling with the quota sampling method. Tests carried out in this study include validity tests, reliability tests, model tests, and hypothesis testing. The analytical tool used is multiple linear regression. The results of this study indicate that leadership has a positive and significant effect on organizational commitment and organizational justice has a positive and significant effect on organizational commitment. This research has theoretical and practical implications.